Pruning management in blueberries and its effect on Lasiodiplodia spp. - León-Alcántara, Eduardo Enrique; Flores-Coronel, Lelis Eudith; Campoverde-Ventura, Giannina; Vásquez-Mora, Sunnis Adis (Revista Mexicana de Ciencias Agrícolas, 2026)
Blueberries (Vaccinium spp.) are a fruit with recognized medicinal properties and rich in antioxidants, vitamins, and fiber, which has boosted their global demand. Nonetheless, the crop faces certain challenges, such as ‘dieback’ by the fungus Lasiodiplodia spp., which can severely reduce production. To mitigate this disease, regular pruning is essential, improving air circulation and sunlight penetration, creating a less favorable environment for fungi. The objective of this research was to determine the effects of pruning management on the incidence of Lasiodiplodia spp. in crops of blueberries (Vaccinium corymbosum L.) var. Biloxi. The study was conducted in Piura, Peru, in 2022; different pruning treatments were evaluated in plants affected by Lasiodiplodia spp., using a CRD with five treatments and a control, with a sample size of two hundred plants; likewise, Duncan’s test was used to compare the effects. The results showed that more aggressive pruning, which removed more leaves and sap drawers, resulted in increased shoot growth due to the plants’ ability to regenerate in the face of severe stress, thereby stimulating greater production of growth hormones, such as cytokinins. Additionally, plants with aggressive pruning exhibited a higher incidence of Lasiodiplodia spp., suggesting that treatments T1 and T0 were the most balanced options. It was concluded that a combination of pruning techniques is essential to maintain the health of blueberry crops against the attack of Lasiodiplodia spp.
Keywords: Vaccinium corymbosum; canker; cultural control